(untitled) (TAJ: Journal of Teachers Association, 2009)
This study was aimed to find out the variations of the femoral head diameters in relation to sex in Bangladeshi people. The study was based on 123 paired human femurs (radiological view) of which 52 were male and 71were female. It was observed that the mean vertical and transverse diameters of the head of the male femur were significantly greater than that of female (P<0.001).No statistical significant difference was present between the measurement of the right and left side of the same sixth identification points that were derived from the vertical and transverse diameters of the head of the femur were higher in males than in females. The results showed that diameters of the femoral head as well as the identification points that are derived from them are of use in sex identification. The present study is of value to the forensic experts, orthopaedicians and prosthetists as it gives the idea about the dimensions of the femoral head in the present area. doi: 10.3329/taj.v18i2.3172 TAJ 2005; 18(2): 84-88